(untitled) (JS (JURNAL SEKOLAH), 2020)
Abstract: History subjects are one of the adaptive group subjects to support productive abilities. Teachers deal more with strategy than providing information. The teacher’s job is to manage the class as a team that works together to find something new for class members (students). The use of interactive multimedia, one of which will make a big contribution, especially in increasing the activities and learning outcomes of history class X TKJ students. From the results of observations in the first cycle, 28.86% of students ’completeness was obtained, while in the second cycle 72.92% of students’ completeness in learning activities, while student learning outcomes reached 92.92%. Here there is an increase of 44.06% student completeness. The use of interactive multimedia is not only up to cycle II, but can be used continuously to obtain maximum results Keywords: interactive multimedia, activities, learning outcomes Abstrak: Mata pelajaran sejarah, merupakan salah satu mata pelajaran kelompok adaptif sebagai penunjang kemampuan produktif.Guru lebih banyak berurusan dengan strategi dari pada memberi informasi. Tugas guru mengelola kelas sebagai sebuah tim yang bekerja bersama untuk menemukan sesuatu yang baru bagi anggota kelas (siswa). Penggunaan multimedia interaktif salah satunya yang akan memberikan kontribusi yang besar terutama pada peningkatan aktivitas dan hasil belajar sejarah siswa kelas X TKJ. Dari hasil obsevasi pada siklus I diperoleh 28.86 % ketuntasan siswa, sedangkan pada siklus II 72.92 % ketuntasan siswa pada aktivitas belajar, sedangkan hasil belajar siswa mencapai 92.92 %. Disini terjadi peningkatan sebesar 44.06 % ketuntasan siswa. Penggunaan multimedia interaktif ini tidak hanya sampai siklus II saja, tetapi bisa digunakan secara kontiniu untuk memperoleh hasil yang maksimal Kata Kunci : multimedia interaktif, aktifitas , hasil belajar